Problematika Orang Tua dalam Pendampingan Kegiatan Belajar dari Rumah (BDR) di TK DWP Sukoanyar - Nia Kusmiyati; Norma Diana Fitri; Indaria Tri Hariyani (Universitas Islam Tribakti Lirboyo Kediri, 2021)
Learning From Home Activities (BDR) is an alternative program for providing educational services to children during the Covid-19 pandemic. This study was inspiredby parental complaints about their children's BDR activities. The purpose of this research is to determine the form of BDR activities, the role of parents in assisting children's BDR activities, and the problems that parents face when assisting children'sBDR activities in TK DWP Sukoanyar. The method used in this study is a descriptive qualitative approach with data collection techniques such as interviews, observation, and documentation. The data was then triangulated. The findings of this study indicatethat TK DWP Sukoanyar engages in BDR activities using both online and offline methods. The online method makes use of Whatsapp and Zoom, whereas the offline method makes use of books. This could be concluded that now the role of parents in assisting children's BDR activities in TK DWP Sukoanyar has been carried out quite well. However, several problems have been found by parents in carrying out this role in assisting children's BDR activities, namely the lack of understanding of parents to carry out theirroles as teachers due to educational factors, additional living costs in the form of credit and quotas, boredom level of children to study at home, imbalance between the roles of fathers and mothers, and limited facilities at home